Evaluation of visual electrophysiological test in obstructive sleep apnoea - Ng, Seok Hui (2016)
Introduction Obstructive sleep apnea (OSA) is a life-threatening, sleep-related breathing disorder characterized by partial (hypopneas) and complete pauses (apneas) in breathing that last at least 10 seconds during sleep. As a consequence, the blood oxygen saturation may fall, with resulting in a hypoxia state. OSA has been associated with ocular conditions such as non-arteritic anterior ischemic optic neuropathy (NAION), papilloedema, glaucoma and central retinal vein occlusion. Visual electrophysiological tests like pattern visual evoked potential (PVEP) and pattern electroretinogram (PERG) may be able to detect functional impairment of the retina and visual pathway in OSA patients. Objective To compare the PVEP & PERG changes in patients with OSA and control group. We also analyzed the relationship between visual electrophysiological tests with the severity of OSA. Material and methods A comparative cross-sectional study was conducted in Hospital Universiti Sains Malaysia involving 40 samples of OSA patients and 31 control subjects. A complete ocular examination was performed which include visual acuity, anterior and posterior segment. PERG (0.8⁰ checks size) and PVEP (0.25⁰ checks size) were conducted bya single technician. Independent t-test, Mann-Whitney, Kruskal-Wallis Test, Pearson and Spearman‘s correlation test were used in statistical analysis. Results There were statistically significant reduction of the PVEP P100 wave amplitude (P<0.001) and delay in PVEP P100 and N75 latency (P<0.001) in the OSA group. Among OSA patients, we also observed a significant reduction of the P50 wave amplitude (P<0.001) in PERG, compared to the control group. However, there is no finding on association of PVEP and PERG according to severity of OSA . There was no significant differences of PERG latency were observed in either group. There was no significant correlation in PVEP or PERG between OSA patients with different disease severity except PVEP latency N75 which is statistically significant but fair negative correlation Conclusion OSA patients have significant abnormalities in VEP amplitude and latency, and ERG amplitude, suggesting that hypoxia may be a pathophysiology in these conditions. There were no significant relationships between PVEP and PERG in AHI of OSA patients